2011
DOI: 10.1590/s0104-14282011005000044
|View full text |Cite
|
Sign up to set email alerts
|

Redução da massa molecular e funcionalização do poli(3-hidroxibutirato-co-3-hidroxivalerato) (PHBHV) via hidrólise ácida e transesterificação com glicóis

Abstract: Resumo: Neste trabalho foi realizado um estudo da redução da massa molecular do poli (3-hidroxibutirato-co-3-hidroxivalerato) (PHBHV) usando duas metodologias: hidrólise ácida com ácido clorídrico e transesterificação com etilenoglicol e hexilenoglicol. Foram investigados os parâmetros do processo: tempo, temperatura e concentração de catalisadores. Todas as metodologias estudadas geraram biopolímeros com massa molecular reduzida e funcionalizados com grupos hidroxila e carboxila terminais. Foram comparadas as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…PHB and PHBHV molar mass reductions can be obtained by thermal degradation [34,41], acid hydrolysis [4,[42][43], transesterification with glycols [44] reduction with NaBH 4 [6,45] or also in vivo esterification with PEG [46].…”
Section: Molar Mass Reduction and Further Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHB and PHBHV molar mass reductions can be obtained by thermal degradation [34,41], acid hydrolysis [4,[42][43], transesterification with glycols [44] reduction with NaBH 4 [6,45] or also in vivo esterification with PEG [46].…”
Section: Molar Mass Reduction and Further Modificationsmentioning
confidence: 99%
“…The studies indicated that the use of low molar mass PHBHV was more favorable in increasing entrapment and entrapment efficiency and enzyme activity [46]. Montoro, SR. et al [42] used the methods of acid hydrolysis and trans-esterification with ethylene and hexyleneglycol and also by reductions with sodium borohydride [4,6] to obtain PHBHV with molar mass reduced in order to develop materials suitable to be used as carriers in active systems. Liu,Q.…”
Section: Molar Mass Reduction and Further Modificationsmentioning
confidence: 99%